Upaya Pembentukan Karakter Siswa Melalui Kegiatan Organisasi Siswa Intra Sekolah (Osis) Di SMP Negeri 6 Singaraja - I Gusti Ayu Ngurah Trisna Widya Ningrum; I Wayan Lasmawan; I Nengah Suastika (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effort to shape student character through the activities of intra-school student organizations (OSIS) in SMP Negeri 6 Singaraja. The research method used in this study is a qualitative descriptive research method that is research with direct decrease in spaciousness. In this study the determination of subjects and research objects using purposive sampling techniques, is data retrieval with several considerations so that the data will be more representative of all. Data collection using the method of observation, interviews, documentation and study of literature. Checking the validity of the data is obtained through data triangulation, method triangulation and source triangulation. The results of this study indicate that: (1) Character values applied through OSIS activities in which almost 18 character values are applied to students or all school members according to their respective portions. (2) One of the efforts to form student character through student council activities by participating in various activities that have been designed by student council, because in these activities can form student characters including participating in LKDS (Student Leadership Basic Training), in addition to other student council activities that can shape the character of students by conducting raids on every Saturday able to improve the discipline of all students in the school. (3) The obstacles in the effort to form student character through student council activities include lack of confidence in the student council members or student council organizers in carrying out activities or participating in activities, the difficulty of regulating hours between playing, studying, and organizing, this happens because of background and economics differentstudents.